2015
DOI: 10.1590/01047760201521031658
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação Da Teoria Das Opções Reais Na Análise De Investimentos Em Sistemas Agroflorestais

Abstract: RESUMO:Neste trabalho, compararam-se os valores gerados pela análise econômica tradicional (Valor Presente Líquido -VPL) com as Opções Reais. Aplicou-se o método proposto por Copeland & Antikarov para opções arco-íris, devido às três variáveis estocásticas selecionadas, com decisão de abandono caso o valor do projeto com flexibilidade fosse menor que o valor do ativo subjacente. Possibilitando a geração do valor de flexibilidade para que o empreendedor tenha mais confiança na tomada de decisão no momento de in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…However, according to Correia Neto (2009), the values that can occur never reach the extreme point of the tree because they follow reversion to the mean and are always close to the average. Moreover, according to Joaquim et al (2015), the binomial arrangement of the values in the event tree makes it impossible to visualize the other possible values within the interval between the minimum and maximum of the selected variable.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Correia Neto (2009), the values that can occur never reach the extreme point of the tree because they follow reversion to the mean and are always close to the average. Moreover, according to Joaquim et al (2015), the binomial arrangement of the values in the event tree makes it impossible to visualize the other possible values within the interval between the minimum and maximum of the selected variable.…”
Section: Resultsmentioning
confidence: 99%
“…The positive NPV indicated that if implemented, this integration system would cover its implementation and maintenance costs (JOAQUIM et al, 2015), i.e., the generated revenues would be sufficient to cover the expenses necessary to produce, and it would be possible to recover the financial capital invested in the integrated production system.…”
Section: Economic Feasibility Analysismentioning
confidence: 99%
“…Since the event tree presents binomial disposition, it is not possible to visualize the other values that can occur in the interval between the minimum and the maximum of the variable under study (Joaquim et al, 2015). Without inserting managerial flexibility in the analysis of the event tree, the value obtained corresponds to the NPV initially calculated.…”
Section: Event Treementioning
confidence: 99%
“…As shown in Figure 5, the value of the abandon option is lower in the initial investment periods, gradually increasing over the planning horizon. In projects that require investment in all periods of the planning horizon, such as the study investment, the value of abandonment is cumulative and increasing (Joaquim, 2015).…”
Section: Abandonment Valuementioning
confidence: 99%